Controlling the growth of single-walled carbon nanotubes using alcohol catalytic CVD method - Asyadi Azam, Mohd; Mohamed, Mohd Ambri; Shikoh, Eiji; Fujiwara, Akihiko (2010)
Single-walled carbon nanotubes (SWCNTs) were grown from Co catalyst thin-films using alcohol catalytic CVD method at different CVD process times. Structural properties of grown SWCNTs have been investigated by means of Raman spectroscopy with various laser excitations. SWCNTs were growing until t = 20 min, but Raman intensity of SWCNTs decreased for the longer CVD process times. The quality level of as-grown SWCNTs also decreased at the longer CVD process times, likewise the Raman intensities trend. From the Raman RBM intensity analysis, relatively thinner SWCNTs are likely proposed to be burning out during the longer CVD process times (t = 30 to 115 min), suggesting lower stability in their structures. This research work suggests that the Co catalyst poisoning and SWCNTs burning phenomenon occurs when the CVD process time is more than 20 min.